2008
DOI: 10.1524/ract.2008.1526
|View full text |Cite
|
Sign up to set email alerts
|

Determination of trace elements in iron minerals by instrumental and radiochemical neutron activation analysis

Abstract: (FeS 2 ) and chalcopyrite (CuFeS 2 )] minerals using the k 0 -method of neutron activation analysis in both forms: instrumental (k 0 -INAA) and radiochemical (k 0 -RNAA) was suggested. In order to avoid interferences from iron on the determination of elements present in trace levels, radiochemical separation was made. Determination of the investigated elements in the aqueous phase was performed by k 0 -RNAA after extraction of iron by isoamyl acetate (IAA) and diisopropyl ether (DIPE) from hydrochloric acid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…1. Ratio between k 0 -RNAA (extraction into DIPE and IAA) and k 0 -INAA for REE in hematite [36] In addition, a high recovery of another 12 elements (Ag, Ba, Cd, Co, Cr, Cs, Hg, In, Na, Nd, Sc and Zn) in the aqueous phase after Fe removal with DIPE was also found. Moreover, after the extraction of Fe, the limits of detection for several elements (Ag, Ba, Ca, Ce, U, W) became lower compared to the corresponding values in the k 0 -INAA.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…1. Ratio between k 0 -RNAA (extraction into DIPE and IAA) and k 0 -INAA for REE in hematite [36] In addition, a high recovery of another 12 elements (Ag, Ba, Cd, Co, Cr, Cs, Hg, In, Na, Nd, Sc and Zn) in the aqueous phase after Fe removal with DIPE was also found. Moreover, after the extraction of Fe, the limits of detection for several elements (Ag, Ba, Ca, Ce, U, W) became lower compared to the corresponding values in the k 0 -INAA.…”
Section: Resultsmentioning
confidence: 80%
“…It could be concluded that the major and trace elements content in three iron minerals using the k 0 -INAA could be determined before and after quantitative removal of Fe by liquid-liquid extraction [36]. It was found that Au, Se, Te, Mo and Sb show similar behaviour in hydrochloric acid solution to Fe, and they could be removed with high efficiency.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…It has a high sensitivity and good accuracy and it is non-destructive. This method was applied by many authors in order to achieve accurate knowledge of the iron content and the concentrations of trace elements present in iron ores [6], high purity iron as a certified standard material from Iron and Steel Institute of Japan [7], iron certified reference materials using multiple gamma-ray detection method [8], iron-based alloys [9], iron minerals [10] and for the analysis of minor constituents in steels [11]. In previous studies [12,13] INAA was applied for the determination of the compositional scheme of some materials -iron ores and pellets from different reBrought to you by | University of Iowa Libraries Authenticated Download Date | 5/26/15 2:38 PM gions of the world (Australia, Brazil, CSI, India, Mozambique, Romania, Ukraine, Venezuela), slag, cast iron and steels -used in ferrous metallurgical processes in Iron and Steel Integrated Works (ISIW) of Galati, Romania.…”
Section: Introductionmentioning
confidence: 99%